(untitled) (Research, Society and Development, 2023)
The objective of this scientific article was to evaluate the control of energy waste in the Dean of Development and Personnel Management at the Federal University of Pará (PROGEP/UFPA), seeking to address the problem of environmental education and understand the perceptions of technical administrative staff in education that develop activities in this sector. This research corroborates and confirms the implementation of environmental management activities and actions in Federal Higher Education Institutions, whose object is UFPA, an institution of great importance due to its location in the central part of the Amazon. As a methodological procedure, bibliographical, documentary and field research were used, with the applicability of a questionnaire to administrative technical staff in education at PROGEP, highlighting which forms of energy saving are used in this administrative area and, therefore, as an analysis of official documents of UFPA in relation to this topic. The most significant and relevant results show that the majority of positive responses concern issues of environmental sustainability in the institutional context, but only in relation to the issue of access to information on the economic use of facilities, we found in this research that the majority of technical staff administrative staff in education (approximately 89%) do not have access to this information, which in general could negatively impact the sustainable development practices and economic efficiency of this renowned institution.